2021
DOI: 10.3390/pharmaceutics13101676
|View full text |Cite
|
Sign up to set email alerts
|

Manipulations of Oral Medications in Paediatric Neurology and Oncology Care at a Swedish University Hospital: Health Professionals’ Attitudes and Sources of Information

Abstract: Oral administration of medications to children requires age-appropriate dosage forms and strengths. In this study, we: (i) assessed the extent of oral dosage form manipulations, (ii) documented how it is carried out, and (iii) examined the attitudes and sources of information regarding the handling from healthcare professionals. Prospective reviews of electronic records, ward observations, and clinician surveys were performed at a paediatric neurology ward and a paediatric oncology ward in Sweden during April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Studies conducted in a children's hospital in the Netherlands and pediatric wards in a German hospital show that manipulation was necessary for 37% of oral medicine prior to administration [7,8]. Similar studies conducted in Norway and Sweden found a lower manipulation prevalence of 17% and 15.5%, respectively, for orally administered pediatric medicines [5,6]. The lower manipulation rate could be explained by a difference in the definition of drug manipulation.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Studies conducted in a children's hospital in the Netherlands and pediatric wards in a German hospital show that manipulation was necessary for 37% of oral medicine prior to administration [7,8]. Similar studies conducted in Norway and Sweden found a lower manipulation prevalence of 17% and 15.5%, respectively, for orally administered pediatric medicines [5,6]. The lower manipulation rate could be explained by a difference in the definition of drug manipulation.…”
Section: Introductionmentioning
confidence: 70%
“…Manipulation of marketed drugs, e.g., crushing or splitting tablets or diluting a solution, often holds two specific reasons, namely, to acquire the needed dosage strength, or to adapt an unsuitable dosage form, i.e., poor swallowability or palatability of the dosage form. A combination of these reasons also occurs [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of manipulations include the splitting of tablets, crushing and dissolving tablets in liquids, opening capsules and cutting suppositories 1 . Most studies on the manipulation of medicines in the paediatric setting are observational studies for short time periods with results ranging from 10% to 57% of all administrations being manipulated 2–5 . A study conducted in a Swedish paediatric university hospital concluded that there is still a lack of suitable dosage forms and strengths for paediatric patients 6 …”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of manipulated doses, including those made to facilitate drug administration, ranged from 11% in adolescents to 64% in toddlers, with an overall average frequency of 16% [ 9 ]. These results contradict earlier reports where children older than six years have the highest frequency of manipulations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%